Kadar insulin-like growth factor-1, ghrelin ASI, dan peningkatan berat badan bayi pada ibu menyusui obesitas dan normal - Desriati Sinaga; Eny Yantri; Yusrawati Yusrawati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2018)
Background: Obesity is one of the factors that trigger the incidence of non-communicable diseases and increase morbidity rates in mothers and infants. Ghrelin hormone in breast milk serves to stimulate appetite in infants as well as release factors for growth hormone (GH). Insulin-like growth factor 1 (IGF-1) hormone in breast milk plays a role in increasing the length of bone and muscle mass of infants and mediators of GH work. Obesity can affect baby's weight gain, ghrelin and IGF-1 hormone levels in breast milk.Objective: Analyzes the association of IGF-1 and ghrelin levels of breast milk with baby's weight gain between obese and normal mothers.Method: Observational study with cross sectional design on 40 breastfeeding mothers and their infants in the work area of Andalas Health Center, Ikur Koto Health Center and Puskesmas Lubuk Buaya Padang City with consecutive sampling technique from August to November 2017. The examination of IGF-1 and ghrelin levels was conducted at the University's Biomedical Laboratory Andalas with ELISA method. Weight gain is obtained from first month infant weight loss with infant birth weight. Data analysis used independent t-test and Pearson test.Results: There was a difference in IGF-1 levels in breast milk (p=0.00) between obese and normal mothers. There was no difference in ghrelin levels of breast milk (p=0.90) between obese and normal mothers. There was a difference in weight gain between obese and normal mothers (p=0.02). There was no significant association between IGF-1 and ghrelin levels of breast milk with an increase baby weight gain between obese and normal mothers.Conclusion: There was no significant association between IGF-1 and ghrelin levels of breast milk with an increase baby weight gain between obese and normal mothers.